A influência do uso dos bifosfonatos na Odontologia: revisão de literatura - Prearo, Tamires Cristina [UNESP] (2014)
Currently the installation of implants has been widely published in order to rehabilitate the oral condition of the patient by providing a more favorable occlusion. However, despite its success, problems such as osteonecrosis of the jaw can affect the success of these procedures, which is reported as a complication bone necrosis that occurs in the oral cavity so as caused by a poor bone healing due, for example, using bisphosphonates associated with traumatic surgical procedure. Bisphosphonates have been used in large quantities for treatment of bone diseases, however, the literature suggests that these medications can be a potent cause of osteonerose but still not sure how this mechanism occurs. It is suggested from the process of pathogenesis which bisphosphonates inhibit osteoclast function leading to a decrease in bone resorption and inhibition of natural bone turnover. This leads to a reduction of some mechanical characteristics of the bone, as well as areas of accumulated microfractures. Therefore, there is a need to study the connection between bisphosphonates and osteonecrosis, recognize signs and symptoms of osteonecrosis, patients at risk, and develop preventive and therapeutic measures. Has not yet been discovered the treatment of this complication, it is advisable that the patient is properly evaluated, that the dentist ask for laboratory examination (CTX) to assist in the diagnosis, plus there is a dialogue between the doctor and the dentist for a better way to prevention and treatment, improving the quality of life of patients